Expression of HvCslF9 and HvCslF6 barley genes in the genetic background of wheat and their influence on the wheat β‐glucan content. (11th June 2013) - Cseh, A.; Soós, V.; Rakszegi, M.; Türkösi, E.; Balázs, E.; Molnár‐Láng, M.
Abstract The dietary fibre (1, 3;1, 4)‐β‐d‐glucan (β‐glucan), is a major quality parameter of cereals. Grain β‐glucan content is the most important factor from the aspect of human health maintenance. The grain of barley (Hordeum vulgare) is one of the most important β‐glucan sources having a β‐glucan content 10 times higher than that of wheat (Triticum aestivum). Winter wheat/winter barley 'Mv9kr1'/'Igri' 1HS ditelosomic and 'Mv9kr1'/'Igri' 7H disomic addition lines carrying the HvCslF9 and HvCslF6 barley genes, respectively, were used to investigate the additive effect of barley cellulose synthase‐like genes on the wheat β‐glucan content. A significantly higher β‐glucan level was detected in the leaves and grains of the wheat/barley 1HS and 7H addition lines compared to the control wheat line. The expression of the HvCslF9 and HvCslF6 genes in the genetic background of wheat was also determined by quantitative RT‐PCR. The expression pattern of the HvCslF9 gene transcript showed a gradual increase throughout grain development, while the HvCslF6 gene was normally transcribed at relatively high levels. In leaves, the transcript of the HvCslF9 gene could not be detected at the end of tillering, while the HvCslF6 gene was still strongly expressed at this time in the 7H addition line. This study mapped the HvCslF9 gene to the short arm of the 1H chromosome. The HvGlb1 barley gene, encoding (1, 3;1, 4)‐β‐d‐glucan endohydrolase isoenzyme EI, is possibly involved in the regulation of the β‐glucan level during grain development. Previously this was also mapped to the barley 1H chromosome, and this study suggested that it was located on the 1HL chromosome arm. It was also concluded that the independent expression of the HvCslF9 gene in the wheat background resulted in a slight increase in the β‐glucan content. The results provide new insights into the expression and regulation of the HvCslF genes in the genetic background of wheat and indicate that cisgenesis can be used to increase the leaf and grain β‐glucan content in wheat.